THE INFLUENCE OF PRICE AND SERVICE QUALITY ON PURCHASE DECISION : A CASE STUDY OF BUYERS AT PARUNG ORNAMENTAL FISH MARKET, BOGOR - Masdiansyah, Hendry; Sukatmajaya, Ahmad (Kinerja, 2025)
This study aims to analyze the influence of price and service quality on ornamental fish purchase decisions at the Parung Ornamental Fish Market in Bogor. The method used was a quantitative approach with multiple linear regression analysis and classical assumption testing. The population in this study was ornamental fish buyers at Parung Market. This study used a questionnaire as a data collection instrument with a sample size of 140 respondents, and data processing was carried out using SPSS. The test results showed that the data met the classical assumptions and the regression model was significant. Price (β = 0.500) and service quality (β = 0.340) have a positive and significant effect on purchasing decisions (Sig. < 0.05). The R² value of 0.721 indicates that these two variables are able to explain 72.1% of the variation in purchasing decisions, while the remaining 17.9% is explained by other factors outside the model. The F test also shows that price and service quality simultaneously have a significant effect on purchasing decisions (F = 189.681; Sig. = 0.001). Thus, it can be concluded that price and service quality partially and simultaneously have a positive and significant effect on purchasing decisions for ornamental fish at the Parung Bogor Ornamental Fish Market. This model can be used as a basis for making marketing strategy decisions in the traditional ornamental fish trade sector.